FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN NON-KEUANGAN DI INDONESIA - Yoseph Anastasius Didik Cahyanto; Michelle Maria Madelyn (E-Jurnal Akuntansi TSM, 2022)
This study is aim to obtain evidence about the influence of motivational bonus, leverage, firm size, size of an audit committee, independent commissioners, institutional ownership, managerial ownership, free cash flow, firm growth, and audit quality as independent variables on earnings management as a dependent variable in Indonesian non-financial companies. This research used non-financial companies that listed in Indonesia Stock Exchange during 2018-2020 as the population. There are 104 companies, with 312 total data that meet the criteria. This research using purposive sampling method and used multiple regression method to analyze the data. The result shows that motivational bonus, leverage, free cash flow, and growth have influence on earnings management, so the higher the motivational bonus and growth the higher earnings management and the higher the leverage and free cash flow the lower earnings management, while other independents variable such as independent commisioner, firm size, size of an audit committee, institutional ownership, managerial ownership, and audit quality have no influence on earnings management practice in the company